Penerapan Konsep Green Practices dalam Pengembangan Produk Halal yang Berkelanjutan - Mulyawati, Nindi Azizah; Setiawan, Firman (Prodi Perbankan Syariah FAI UMT, 2024)
Human awareness of environmental problems encourages a determination to start changing lifestyles to be more environmentally friendly. This is seen as a business opportunity for some people. Therefore, many entrepreneurs are starting to apply various innovative methods by implementing environmentally friendly practices in their business operations. The aim of this research is how MSME business actors in Sumenep district implement the 3 components of green practice (green action, green food, green donation) in developing halal products (study of food and beverage products in Sumenep district). The method used in this research is a qualitative descriptive method with data sources obtained through interviews and observations. Data analysis in this study used QSR Nvivo software. The results of this research indicate that the implementation of environmentally friendly practices in developing Halal MSME products in Sumenep district focuses on three main components, namely environmentally friendly actions, environmentally friendly food, and environmentally friendly donations. Where MSME halal products will be said to truly meet the green product principles, when they comply with the criteria of these three components.